A produção de sentidos do psicoterapeuta inserido na economia de plataforma: uma análise a partir da psicologia sócio-histórica - Motta, Gabriel Girardi (2023)
The present master's research, entitled The Production of Sense of the Psychotherapist Inserted in the Platform Economy: an analysis from the Sociohistorical Psychology perspective, on the process of platformization of psychotherapists professionals, with the advent of platform economies, aims to study the professional in the contemporary morphology of work and to understand the constitution of meanings, based on the assumptions of Sociohistorical Psychology. To obtain that, it was used the methodology of the Nuclei of Meaning. The main focus of this study was the search of the word with meaning, so that it would be possible for the research to go beyond the phenomenal dimension of the subjects' experience and reach its essence. Since the platformization resembles the phenomenon popularly known as uberization of work, it can bring threats to the professional category, and this research sought to understand what impacts this phenomenon may be causing to the pyschologists. For this, we defined two goals: to understand if platformization affects the psychotherapist's relationship and connection with science and the profession of Psychology, and to identify if platformization generates exploitation and precariousness of the psychotherapists who take part in it.